A qualitative study exploring patients' experiences of standard care or cardiac rehabilitation post minor stroke and transient ischaemic attack. (September 2013) - Hillsdon, Kaye M; Kersten, Paula; Kirk, Hayden JS
Objective: To explore individuals' experiences of receiving either standard care or comprehensive cardiac rehabilitation post minor stroke or transient ischaemic attack. Design: A qualitative study using semi-structured interviews, alongside a randomized controlled trial, exploring the effectiveness of comprehensive cardiac rehabilitation compared with standard care. Interviews were transcribed verbatim and subjected to thematic analysis. Setting: Individuals' homes. Subjects: People who have experienced a minor stroke or transient ischaemic attack and who were partaking in a secondary prevention randomized controlled trial (6–7 months post the event, 17 males, five females; mean age 67 years). Interventions: Not relevant. Main measures: Not relevant. Results: Four themes were identified: information delivery, comparing oneself with others, psychological impact, attitudes and actions regarding risk factor reduction. Participants indicated a need for improved information delivery, specific to their own risk factors and lifestyle changes. Many experienced psychological impact as a result of their minor stroke. Participants were found to make two types of social comparison; the comparison of self to another affected by stroke, and the comparison of self to cardiac patients. Conclusion: Comprehensive cardiac rehabilitation was reported to have positive effects on people's motivation to exercise. Following a minor stroke, many individuals do not recall information given or risk factors specific to them. Downward comparison with individuals who have had a cardiovascular event led to some underplaying the significance of their minor stroke.